Competition and antitrust in internet markets - Justus Haucap; Torben Stühmeier (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
This paper summarizes the peculiarities of online markets and discusses recent antitrust cases related to online markets. Following a brief description of the online markets' characteristics and potential tendencies for concentration the paper first discusses the antitrust allegations and proceedings against Google, before commenting on the most prominent cases related to vertical restraints, including the Apple ebook case and the ECJ's Pierre Fabre case. We also highlight competition issues at the infrastructure level, namely margin or price squeezing of incumbent operators vis-à-vis new ISPs and network neutrality. Finally, policy conclusions and further research questions are discussed in the paper's concluding section.
Keywords: 330; digital markets; Google; E-Book; online markets; net neutrality; vertical restraints